Prevalence of Chronic Kidney Failure and Associated Factors in Patients Treated by Antiretroviral in the National Teaching Hospital of Cotonou - ZANNOU, D Marcel; VIGAN, JACQUES; Azon-Kouanou, A; AGBOTON, BRUNO; Houngbe, CMB; HOUNGBE, FABIEN (My University, 2015)
Objectives: To determine the frequency of the chronic kidney failure (CKF) in people living with HIV (PLHIV) on antiretroviral treatment (ART) and to identify associated factors. Methods: This cross-sectional, descriptive and analytical study, conducted in the Outpatient Centre of PLHIV in the National Teaching Hospital of Cotonou from April to July of 2013. Were included, PLHIV aged over 16 years, taking ART for at least three months and having in their file, creatinine at ART initiation. Creatinine was performed at inclusion in the study. Proteinuria was sought on the strip. Chronic kidney failure was defined as creatinine clearance calculated according to Cockcroft-Gault less than 60mL/min for at least 3 months. Factors associated were searched by logistic regression univariate and multivariate analysis. Confidence intervals were calculated at 95% and alpha level was 5%. Results: A total of 480 patients participated in the study (73.3% women; mean age 41.4 ± 9.16 years, in school: 64.6%). The prevalence of chronic kidney failure was 18.7%. The main factors associated in univariate analysis were age (p<0.001), BMI (p<0.001), educational level (p=0.03), the exposure time to ART (p<0.001) and the loss of kidney function at the initiation of ART (p<0.001); in multivariate analysis: age (p<0.001), sex (p<0.001), the body mass index (p<0.001), the loss of kidney function at ART initiation (p=0.034) and didanosine (p=0.007). Discussion and conclusion: The prevalence of chronic kidney failure in patients receiving ART is high. The creatinine serum in biological monitoring in the ART or better to determine the glomerular filtration rate among PLHIV at least every six (6) months remains a necessity.
Keywords: Antiretroviral treatment; Benin; Chronic kidney failure; Clearance of creatinine; HIV; Logistic regression; Prevalence